Land Use in RW 003 Benteng Village - Sari, Diana Novita; Bimo, Widhi Ariyo (Jurnal Pengabdian Nusantara, 2023)
Use of the yard will provide sustenance. Because in principle, humans lived in need of these items of food, and of what they worked to provide the necessities of life. This activity aims to motivate the community to make the most of their homeland, as it will become an economically valuable plant and be able to increase family economic incomes and meet daily needs. The method used in acquiring information is descriptive. Based on land conditions for the Benteng village rt 002/ rw 003 have the opportunities and the potential to benefit fresh vegetables as healthy and nutritious food for families and communities. The results of the exploitation of yards already available to families and communities are a benefit derived from the optimization of the yard.